Multicriteria approach to evaluation of coconut shell charcoal using quality and recovery information - Casis, Erlinda Dado (2007)
Multi-criteria Decision Analysis (MCDA) is a procedure aimed to support decision maker whose problem involved numerous and conflicting evaluations. MCDA has a lot of models but the study used Analytic Hierarchy Process (AHP) to determine the weighs of the attributes. The study dealt with two types of information, soft and hard. Hard information is the data from the experiment of the analysts of Philippine Coconut Authority (PCA) Region XI while the soft information is the comparison of attributes and assessment of data done by the experts. The data includes 45 samples with their performance in each attribute. Thirteen attributes were considered in the experiment and those are the moisture content, iodine number, apparent density, bulk density, ash, volatile, magnetic particle, fixed carbon, hardness, particle size in 4 mesh, particle size on 8 mesh, particle size thru 8 mesh and recovery. Recovery was included as attribute to satisfy the goal of the farmers to produce more charcoal. The experiment is for the suppliers and buyers of activated carbon to increase competence and gain more profit. Three applications were considered in this study and one expert in each application was assigned to evaluate the data prior to each application. This study had developed a method of assessment with the use of soft and hard information in evaluation the alternatives in determining the optimal coconut shell charcoal and determined the coconut shell charcoal prior to coconut shell?s variety, location, storage area and number of weeks of storage that can give optimal quality and recovery